Keragaan Pertumbuhan dan Produksi Beberapa Varietas Kedelai (Glycine Max L.) pada Gawangan TBM Kelapa Sawit - Haitami, Ahmad; Indrawanis, Elfi; Ezward, Chairil; Wahyudi, Wahyudi (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2020)
This research was aims to determine the growth and production performance of several soybean varieties (Glycine max L.) in the palm oil palm oil compartment. The specific objectives of this study are 1) to determine the growth and production performance of several soybean varieties grown in the oil palm gates of TBM. 2) Determine the morphological characteristics of the appearance of some soybean varieties. This research has been carried out in the Experimental Garden of the Faculty of Agriculture, Kuantan Singingi Islamic University for 4 months. This study used a Completely Randomized Block Design (RCBD) consisting of 5 treatment levels and 3 groups, so that 15 unit experimental units were obtained. The treatment level consists of A = Variety Demas 1, B = Dena Varieties 1, C = Argo Mulyo Varieties, D = Devon Varieties 1, E = Devon Varieties 2. The results of the study were statistically tested using SAS version 9.0. give real influence. Based on the results of further tests with Duncan Multiple Range Test (DMRT) at a level of 5%, the plant height parameter of Devon 1 variety was significantly different from other varieties, the total number of pod parameters of Demas 1 variety was significantly different from other varieties, the grain weight parameters and the weight of 100 grains of Devon 2 variety are significantly different from the varieties of Argo Mulyo, Devon 1, Dena 1, and Demas 1.